Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1016/j.jtcvs.2011.09.049
|View full text |Cite
|
Sign up to set email alerts
|

Training residents in off-pump coronary artery bypass surgery: A 14-year experience

Abstract: OPCAB is a safe and reproducible surgical technique that can be taught successfully to cardiothoracic trainees. Clinical outcomes are unrelated to level of supervision or seniority of trainees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…These findings are consistent with previous studies and add to the body of evidence that exposing trainees to off-pump techniques is safe and reproducible. 12,13 Previous studies comparing outcomes between consultant and trainee surgeons have been limited, to some degree, by the tendency of consultant surgeons to select the more complex and higher risk cases. In this series, however, the baseline characteristics of the trainee and consultant surgeon groups were similar with comparable Euroscore and number of grafts performed.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with previous studies and add to the body of evidence that exposing trainees to off-pump techniques is safe and reproducible. 12,13 Previous studies comparing outcomes between consultant and trainee surgeons have been limited, to some degree, by the tendency of consultant surgeons to select the more complex and higher risk cases. In this series, however, the baseline characteristics of the trainee and consultant surgeon groups were similar with comparable Euroscore and number of grafts performed.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Although some of these studies have looked at specific types of operations such as off-pump revascularization or have documented the progress of resident learning as demonstrated by a decrease in the time it takes a trainee to perform a certain task, none of them have routinely provided robust data about the degree of trainee independence. [8][9][10] The majority of these studies do not comment on attending/ resident overlap and have not systematically examined many preoperative, perioperative, and postoperative parameters. [11][12][13] The purpose of this study was to compare postoperative outcomes of 2 similar surgical patient cohorts whose operations were performed entirely by an attending surgeon or by a physician in training.…”
Section: See Editorial Commentary Page 2066mentioning
confidence: 99%
“…Performing MAG is undoubtedly technically demanding and patient's safety should always be a concern when training young surgeons. The effect of training on clinical outcome after cardiac surgery has been the subject of previous publications [14][15][16][17]. However, to the best of our knowledge, this is the first study which compared outcomes in patients undergoing CABG with MAG performed by residents versus attending surgeons and we found that the two groups had comparable short term outcomes and long term survival.…”
Section: Discussionmentioning
confidence: 66%